Little quick fix research question - O'Leary, Zina (Los Angeles Sage Publications, 2018)
Teaches students how to find their interest, hone it to a topic, and turn it into a research question that is relevant, interesting, and researchable.--
Section 1. What is the power of the research question? -- Section 2. What topics are right for research? -- Section 3. How do i articulate my research question? -- Section 4. Do I need hypothesis? -- Section 5. DIY: Write your research question -- Section 6. How do I Know if my question is any good? -- Glossary. Contents
Keywords: Research; Research -- Methodology; Study skills -- Research; Social sciences -- Research -- Methodology